Public policymaking in Hong Kong : civic engagement and state-society relations in a semi-democracy - Lee, Eliza W. Y., 1962- (Milton Park, Abingdon, Oxon : Routledge, 2013)
"This book discusses civic engagement and public policymaking in postcolonial Hong Kong. Utilizing case studies of citizens' advisory committees involving four policy areas - urban planning, social welfare policy, environmental protection, and arts and culture policy - it examines the interaction between the state and civil society, and explores how far the state opens up its policy process for citizens' participation"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Hong Kong (China) -- Politics and government -- Citizen participation; Electronic books